Growing health partnerships in rural and remote communities: what drives the joint efforts of primary schools and universities in maintaining service learning partnerships?. Issue 5 (10th January 2018) - Kirby, Sue; Held, Fabian P.; Jones, Debra; Lyle, David
Abstract : Aim: This study explored the partnership between universities and local primary schools to deliver a classroom-based paediatric communication impairment service provided by undergraduate speech pathology students. It aimed to understand how partnerships work to facilitate programme replication. Background: The partners included universities sending students on rural clinical placement, local host academic units and primary schools who worked together to provide paediatric speech and language services in primary schools in three sites in Australia. Rural and remote communities experience poorer health outcomes because of chronic workforce shortages, social disadvantage and high Aboriginality, poor access to services and underfunding. Methods: The study was in twofold: qualitative analysis of data from interviews/focus group with the partners in the university and education sectors, and quantitative social network analysis of data from an electronic survey of the partners. Findings: Factors supporting partnerships were long-term, work and social relationships, commitment to community, trust and an appetite for risk-taking. We postulate that these characteristics are more likely to exist in rural communities.